EFFECT OF JIGSAW-II TECHNIQUES OF VERTEBRATE ANIMALS REGARDING STUDENTS’ ACHIEVEMENT - Hakan TÜRKMEN (Fırat University, 2019)
Questioning is the most important tool of learning. Today, students have educated as inquirer, producer and sharer in developed countries. For that implication, one of the teaching theories is cooperative teaching method applied by educators. Therefore Jigsaw-II Technique one of the technique of cooperative teaching method was used in this study. In this area the inadequate number of studies of Jigsaw-II Technique carried out in Turkey is required to make such a study. Therefore the purpose of this research is to present the effect of Jigsaw-II techniques in 5th grade elementary students’ academic achievement in science and technology course. The population of this research is 5ht. Grade students of Bornova providence, as sampling group 5/B and 5/C grade students were selected randomly by clustering sampling method from Yeşilçam Elementary school. 20-student each from 5/B class formed experimental group and from 5/C class formed control group. By using Jigsaw-II technique subject of vertebrates were taught for 6 hours (in two weeks) in experimental group. Quantitative and Qualitative methods were applied in this research. After intervention, as a post test the 12-item containing multiple questions and alternative methods questions, such as, concept map, branching tree, constructed grid, academic achievement test was applied and gathering data was analyzed by independent t-test. Moreover 3 open-ended questions were asked to collect data about lesson process. Results showed that there is significantly in favor of the experimental group. Jigsaw-II technique increased the success of students in science and technology course. Meanwhile it was found students have positive thoughts about lesson process.